2010
DOI: 10.1510/icvts.2009.219873
|View full text |Cite
|
Sign up to set email alerts
|

Impact of meteorological conditions on the occurrence of acute type A aortic dissections

Abstract: The impact of meteorological conditions on the occurrence of various cardiovascular events has been reported. The aim of this work was to study the correlations between weather conditions and the occurrence of type A acute aortic dissections (AADs). Between 1997 and 2007, all the medical records of patients who underwent surgery for type A AADs in Toulouse University Hospital (France) were reviewed. The clinical data were confronted with the meteorological data provided by the French national meteorological of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 14 publications
4
36
2
1
Order By: Relevance
“…Several studies have reported a seasonal variation in the incidence of in aortic rupture or dissection, the incidence of aortic dissection and rapture were found to be higher in winter time than in summer in 45.8% of the studies,[3747] and 41.6% of these studies reported significant peak of incidence in spring and autumn. [4857] while only 12.5% failed to find convincing evidence of seasonality in rupture or dissection of aortic aneurysm.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a seasonal variation in the incidence of in aortic rupture or dissection, the incidence of aortic dissection and rapture were found to be higher in winter time than in summer in 45.8% of the studies,[3747] and 41.6% of these studies reported significant peak of incidence in spring and autumn. [4857] while only 12.5% failed to find convincing evidence of seasonality in rupture or dissection of aortic aneurysm.…”
Section: Introductionmentioning
confidence: 99%
“…Studies to date that have examined the association between season and incidence of SA-AoD have yielded mixed results. A statistically significant seasonal variation with a peak in winter was observed by two European case series (France, n ¼ 206, p ¼ 0.018; Switzerland, n ¼ 282, p ¼ 0.011) (Benouaich et al, 2010;Kobza et al, 2002). In contrast, a seasonal variation in incidence was not observed among 570 patients with SA-AoD enrolled in the International Registry of Acute Aortic Dissection (IRAD) between 1996 and 2000 (p ¼ 0.31) (Mehta et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…A vérnyomás szintén emelkedő értéket mutat [23,24,25]. Alacsony légköri hőmérsékleten az aortadissectio-esetek száma is növekvő incidenciát mutat [26].…”
Section: Eredeti Közleményunclassified